2017
DOI: 10.1007/s00259-017-3655-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of the human pulmonary vascular endothelium in pulmonary hypertension: a phase II safety and proof of principle trial

Abstract: PurposeThe adrenomedullin receptor is densely expressed in the pulmonary vascular endothelium. PulmoBind, an adrenomedullin receptor ligand, was developed for molecular diagnosis of pulmonary vascular disease. We evaluated the safety of PulmoBind SPECT imaging and its capacity to detect pulmonary vascular disease associated with pulmonary hypertension (PH) in a human phase II study.MethodsThirty patients with pulmonary arterial hypertension (PAH, n = 23) or chronic thromboembolic PH (CTEPH, n = 7) in WHO funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The specific AM receptor (AM 1 ), a heterodimer composed of CLR and RAMP2, is densely distributed on the vascular endothelium of alveolar capillaries 8,9 . Accordingly, AM is rapidly extracted upon its first passage through the pulmonary circulation 4,6,10 . PB is a molecular tracer derived from human AM that was specifically engineered to bind to the AM 1 receptor to detect PVD 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific AM receptor (AM 1 ), a heterodimer composed of CLR and RAMP2, is densely distributed on the vascular endothelium of alveolar capillaries 8,9 . Accordingly, AM is rapidly extracted upon its first passage through the pulmonary circulation 4,6,10 . PB is a molecular tracer derived from human AM that was specifically engineered to bind to the AM 1 receptor to detect PVD 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In the rat monocrotaline model of PAH, 99m Tc-PB uptake is markedly reduced with a reduction of RAMP2 lung expression 22 . In human PH, a recent phase II study showed that PulmoBind could detect large defects in patients with unoperated chronic thromboembolic PH, as well as smaller heterogenous defects or “drop out” zones in subjects with group I PH 4 . The current study was a first attempt at evaluating the effect of PAH specific therapy on lung 99m Tc-PB uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the indicator-dilution techniques are arduous procedures, not easily performed in the everyday clinical practice. Future studies using “less demanding” techniques at the bedside are needed in an effort to develop clinically useful tests [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a recent nuclear imaging study, using a radiolabeled adrenomedullin derivative, assessed pulmonary blood flow patterns in PAH patients. 77 It showed a completely normal perfusion pattern in one VR-PAH patient on calcium blockers, compared with persistently abnormal perfusion patterns in VN-PAH patients treated with approved PAH therapies ( Fig. 9 ).…”
Section: The Distinct Physiology Of Vr-pahmentioning
confidence: 92%